Effects of Multispecies Synbiotic Supplementation on Anthropometric Measurements, Glucose and Lipid Parameters in Children With Exogenous Obesity: A Randomized, Double Blind, Placebo-Controlled Clinical Trial (Probesity-2 Trial) - Kilic Yildirim, Gonca; Dinleyici, Meltem; Vandenplas, Yvan; Dinleyici, Ener Cagri (Frontiers in Nutrition, 2022)
Studies on the effects of synbiotics on obesity in children are limited. The objective of this randomized double-blind placebo-controlled trial was to test the effects of a multispecies synbiotic during 12 weeks on anthropometric measurements, glucose metabolism and lipid parameters in 61 children with exogenous obesity. All children were treated with a standard diet and increased physical activity and received once daily a synbiotic supplement (probiotic mixture including Lactobacillus acidophilus, Lacticaseibacillus rhamnosus, Bifidobacterium bifidum, Bifidobacterium longum, Enterococcus faecium and fructo-oligosaccharides) or daily placebo for 12 weeks. At baseline, no statistically significant differences existed in anthropometric measurements, glucose and lipid parameters between both groups. We observed changes for anthropometric measures (% reduction comparing to baseline) in both synbiotic and placebo groups. After 12 weeks; changes (% reduction comparing to baseline) in weight (p<0.01), BMI (p<0.05), waist circumference (p<0.05) and waist circumference to height ratio (p<0.05) were significantly higher in the children receiving the synbiotic supplement. There is no difference in glucose metabolism, lipid parameters, presence of non-alcoholic fatty liver disease between both groups after 12 weeks. The daily intake of a multispecies synbiotic in addition to diet and increased physical activity did improve anthropometric measurements: body weight, BMI, waist circumference and waist/height ratio. The supplementation of this synbiotic is an efficient weight-loss strategy above diet and exercise in pediatric obesity.